Forgotten : narratives of age-related dementia and Alzheimer's disease in Canada - Goldman, Marlene, 1963- (McGill-Queen's University Press, 2017)
A groundbreaking comparison of scientific, popular, and literary approaches to provoke new stories of dementia.